R-loops associated with triplet repeat expansions promote gene silencing in Friedreich ataxia and fragile X syndrome. - Matthias Groh; Michele M P Lufino; Richard Wade-Martins; Natalia Gromak (PLoS Genetics)
Friedreich ataxia (FRDA) and Fragile X syndrome (FXS) are among 40 diseases associated with expansion of repeated sequences (TREDs). Although their molecular pathology is not well understood, formation of repressive chromatin and unusual DNA structures over repeat regions were proposed to play a role. Our study now shows that RNA/DNA hybrids (R-loops) form in patient cells on expanded repeats of endogenous FXN and FMR1 genes, associated with FRDA and FXS. These transcription-dependent R-loops are stable, co-localise with repressive H3K9me2 chromatin mark and impede RNA Polymerase II transcription in patient cells. We investigated the interplay between repressive chromatin marks and R-loops on the FXN gene. We show that decrease in repressive H3K9me2 chromatin mark has no effect on R-loop levels. Importantly, increasing R-loop levels by treatment with DNA topoisomerase inhibitor camptothecin leads to up-regulation of repressive chromatin marks, resulting in FXN transcriptional silencing. This provides a direct molecular link between R-loops and the pathology of TREDs, suggesting that R-loops act as an initial trigger to promote FXN and FMR1 silencing. Thus R-loops represent a common feature of nucleotide expansion disorders and provide a new target for therapeutic interventions.